Figurative Language In The Athletic Interview With Peter Drury: A Semantic Study - Utomo, Pambudi; Heriyono, Heri (Lembaga Penelitian Universitas Pasundan, 2025)
The purpose of this research is to identify the types of figurative language and the meanings conveyed through Peter Drury's reflections in an interview with The Athletic. Peter Drury is widely known for his poetic style of football commentary, and his interview provides rich linguistic material to explore how figurative expressions reflect personality, emotion, and professional identity. This study employs a qualitative descriptive method, using a semantic analysis approach to examine the forms and meanings of figurative language found in the interview transcript. The analysis draws on the theoretical framework of Lakoff and Johnson’s (1980) Conceptual Metaphor Theory and other supporting semantic theories relevant to figurative meaning interpretation. The findings reveal that metaphor is the most dominant type of figurative language, comprising 81.8% of the data, followed by personification and idiomatic expressions at 9.1% each. Drury’s frequent use of metaphor, such as describing his sensitivity to criticism as lacking “thick skin,” expresses his vulnerability to public judgment and highlights the emotional burden carried by a public figure. Meanwhile, idioms and personification illustrate his deep connection with language as not only a tool for communication, but also a medium that shapes his identity and creative expression as a commentator. The study concludes that figurative language in the interview contributes significantly to constructing a narrative that resonates emotionally with audiences, revealing Drury’s humility, passion, and philosophical outlook on his career. This research contributes to the fields of linguistics and media discourse studies by emphasizing the role of figurative language in shaping meaningful and memorable public communication.